Interpersonal Meaning of Narrative texts written by undergraduate students of English Education Department in Unsika - Vasya, I Dewa Ayu Made Shaffalya; Samsi, Yoga Setia (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study is going to investigate the interpersonal meaning in Narrative text to discover how interpersonal meaning function is used in narrative text by describing the mood types and the modality of the text. The study employed a qualitative research methodology to explore the mood system provided in narrative text written by undergraduate student's English Education. The researchers take the data from clause as exchange in the narrative text written by undergraduate students. The results of the analysis of the Narrative text written by undergraduate students of English Education are declarative mood, because the writers of the story try to tell something to the reader in fact and reality condition. The first paragraph has a high modality because writing text uses past tense verbs. On the other hand, the second paragraph has a low modality since it is a recount scene of the story. the objectives of the text are analysis the mood type, the researchers finding that declarative mood as a statement by the writers is the most dominant frequency. Then, the analysis of interpersonal meaning in narrative text that shown the writers wants to tell the readers about realistic of the text. Third, the personal pronouns are the most used in the narrative text is the third personal pronouns it means the participant in the story is the author himself. The researchers found only one speech function in narrative text written by undergraduate students of English Education that is statement.